(untitled) (Baghdad Science Journal, 2017)
The adsorption behavior of congo red dye from its aqueous solutions was investigated onto natural and modified bauxite clays. Both bauxite and modified bauxite are primarily characterized by using, FTIR, SEM, AFM, and XRD. Several variables are studied as a function of adsorption including contact time, adsorbent weight, pH, ionic strength, particle size and temperature under batch adsorption technique. The absorbance of the solution before and after adsorption was measured spectrophotometrically. The equilibrium data fit with Langmuir model of adsorption and the linear regression coefficient R2 is found to be 0.9832 and 0.9630 for natural and modified bauxite respectively at 37.5°C which elucidate the best fitting isotherm model. The general shape of the adsorption isotherm of congo red on natural and modified bauxite is consistent with (H-type) on the Giles classification. Different thermodynamic parameters such as Gibb’s free energy, enthalpy and entropy of the on-going adsorption process have also been evaluated. The thermodynamic analyses of the congo red adsorption on natural and modified bauxite indicate that the systems are endothermic in nature